Institutions and fetishes: the "dark matter" problem in social sciences - Mora Jiménez, Henry (2019)
The field of social sciences that studies concepts associated with collective entities, that is the theory of fetishism, has faced the problem of the visibility of the invisible since the beginning. It may include partial collectives (companies, schools, armies) or general collectives, such as the social division of labor, market, and State. It is a world of ghostly subjects that have the possibility to dominate us and that ultimately, and to a great extent, end up doing so. Given the growing role of institutions from the dawn of civilization to the present day regarding the pronounced reduction of direct human relationships in modern societies, if we do not grasp and understand the meaning of these fetishes, we will understand very little of the social universe and its fetishization. This is the reason why we state that these fetishes in social sciences are the equivalent of "dark matter" in astrophysics.